Practice and attitude of pet owners feeding raw based pet diets compared to non-raw based diets - Bjornson, Keyana; Chen, Dale; Environmental Health, BCIT School of Health Sciences (BCIT Environmental Public Health Journal, 2022)
New trends in raw based diets are putting people at a higher risk for becoming ill from pathogens. An outbreak investigation of pig ears containing Salmonella found over 50% of the tested pig ears were positive for the bacteria and 38% of pet treats contained Salmonella. At the time of the outbreak, pet owners became ill with Salmonella which was believed to be from handling the pig ears or from their ill pets that were carrying the bacteria. An outbreak in Italy involving kibble demonstrates there is a risk when feeding raw and non-raw diets.